Race, an delusion: racism and sexism in Brazilian Society - Sepúlveda, Bárbara (Argumentum, 2024)
What is race, and how does it relate to the development processes of capitalism, and to sex/gender in the sense of structuring the state of things, in which better conditions and opportunities are reserved for some, while for others there is only brutality and subalternity? By designating it as a delusion we hope to declare it as null from a biological point of view, and to demarcate its ideological or even neurotic nature. Considering the issue of colonialism and the place of slavery in the formation of the country, we are interested in understanding how such a delusion manifests itself in the Brazilian reality. Intersectionality and qualitative bibliographic research was employed. This led to studies and theory that deal with the historical processes of the racialisation and dehumanisation of Black men and women within the diaspora, and includes Black feminist epistemology.